Recent Advances on Polymeric Beads or Hydrogels as Embolization Agents for Improved Transcatheter Arterial Chemoembolization (TACE) - Chen, Yun-Ping; Zhang, Jiang-Ling; Zou, Yanhong; Wu, Yun-Long (Frontiers in Chemistry, 2019)
Transcatheter arterial chemoembolization (TACE), aiming to block the hepatic artery for inhibiting tumor blood supply, became popular therapy for hepatocellular carcinoma (HCC) patients. Traditional TACE formulation of anticancer drug emulsion in ethiodized oil (i.e. Lipiodol) and gelatin sponge (i.e. Gelfoam) had drawbacks on undesired systemic toxicity and patient tolerance, which were significantly improved by polymeric beads, microparticles, or hydrogels by taking the advantage of elegant design of biocompatible or biodegradable polymers, especially amphiphilic polymers or polymer with both hydrophilic and hydrophobic chains which could self-assemble into proposed microspheres or hydrogels. In this review, we aimed to summary recent advances on polymeric embolization beads or hydrogels as TACE agents, with emphasis on their materials basis of polymer architectures, which are important but have not been comprehensively summarized yet.